Urgensi Bimbingan, Konseling dan Tantangan Dakwah - Rahmiyati Rahmiyati (UIN Antasari Banjarmasin, 2017)
Every human being has hopes, desires, perceptions, emotions and other potentialities, they will bring people to trouble so that they feel life is always in trouble, inferior, helpless, sad, angry and in the end despair. The atmosphere will dim the power of human development in achieving happiness and development toward maturity. In other aspects of human beings as individual beings are also required as social beings. So humans must be able to interact, adapt to themselves and others and must be able to balance the balance between the two. But most humans have the limitations of bringing themselves to the perfection of life untik it is necessary guidance and counseling in human life. Especially for Muslims apart from the above mentioned descriptions of the problem which if faced unfinished will become more serious, that is live life out of the religious signs, then also will nest the inner illness that will eliminate the virtue of a Muslim. For that reason guidance and counseling its existence is very important in education and society in general. In detail the importance of guidance and counseling concerning aspects: psychological, socio-cultural, religious, educational and development of science and technology. In taking the life of every human being must be able to manage the psychological, social and cultural aspects must be able to face the development of science and technology, facing the temptations are misleading